Dermoscopy of Dermatofibrosarcoma Protuberans: What Do We Know? - Gabriela F. Escobar; Caroline K. Ribeiro; Leandro L. Leite; Carolina R. Barone; André Cartell (Mattioli1885, 2019)
Background: Dermatofibrosarcoma protuberans (DFSP) is an uncommon mesenchymal tumor of intermediate malignancy. Its rarity and slow progression often imply a delayed diagnosis. There are few previous reports of dermoscopic features of DFSP and most are single case descriptions. Objectives: To report 2 cases of DFSP and their dermoscopic features, as well as conduct a review of all previous cases published addressing the use of dermoscopy in this tumor. Methods: We conducted a literature search for all dermoscopic cases of DFSP. In addition, we presented 2 additional cases and compared them to the earlier findings. Results: We summarized the main dermoscopic findings of DFSP based on analysis from 32 patients. The most common features of this tumor are the presence of vessels (81%), followed by a pigmented network (78%) and a pinkish background (66%). Conclusions: DFSP can mimic benign lesions and the diagnosis may be challenging. Dermoscopy is an important tool that may enhance clinical suspicion toward the diagnosis of DFSP.